Answered

Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Find the roots of the equation by completing the square: 3x^2-6x-2=0. Prove your answer by solving by the quadratic formula.

Sagot :

luana
Calculating delta: 
Δ=b²-4ac
a=3
b=-6
c=-2
Δ=36-4*3*(-2)=36+24=60
√Δ=√60
Delta is positive so there are two roots:
x1=[tex] \frac{ -b+ \sqrt[2]{delta} }{2a} [/tex]
x1=[tex] \frac{6+ \sqrt{delta} }{2*3} [/tex]=[tex] \frac{3+ \sqrt{15} }{3} [/tex]
x2=[tex] \frac{3- \sqrt{15} }{3} [/tex]
[tex]3x^2-6x-2=0\\\\(\sqrt3\ x)^2-2\cdot\sqrt3\ x\cdot\sqrt3+(\sqrt3)^2-(\sqrt3)^2-2=0\\\\(\sqrt3\ x-\sqrt3)^2-3-2=0\\\\(\sqrt3\ x-\sqrt3)^2=5\iff\sqrt3\ x-\sqrt3=-\sqrt5\ \vee\ \sqrt3\ x-\sqrt3=\sqrt5\\\\\sqrt3\ x=\sqrt3-\sqrt5\ \vee\ \sqrt3\ x=\sqrt3+\sqrt5\ \ \ \ \ |multiply\ both\ sides\ by\ \sqrt3\\\\3x=3-\sqrt{15}\ \vee\ 3x=3+\sqrt{15}\ \ \ \ \ \ \ |divide\ both\ sides\ by\ 3\\\\x=\frac{3-\sqrt{15}}{3}\ \vee\ x=\frac{3+\sqrt{15}}{3}[/tex]



[tex]Prove:\\\\3x^2-6x-2=0\\a=3;\ b=-6;\ c=-2\\\Delta=b^2-4ac\to\Delta=(-6)^2-4\cdot3\cdot(-2)=36+24=60\\\\x_1=\frac{-b-\sqrt\Delta}{2a};\ x_2=\frac{-b+\sqrt\Delta}{2a}\\\\\sqrt\Delta=\sqrt{60}=\sqrt{4\cdot15}=\sqrt4\cdot\sqrt{15}=2\sqrt{15}\\\\x_1=\frac{6-2\sqrt{15}}{2\cdot3}=\frac{3-\sqrt{15}}{3}\ \vee\ x_2=\frac{6+2\sqrt{15}}{2\cdot3}=\frac{3+\sqrt{15}}{3}[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.